Deaths From Plasmodium knowlesi Malaria: Case Series and Systematic Review. (8th January 2019) - Rajahram, Giri S; Cooper, Daniel J; William, Timothy; Grigg, Matthew J; Anstey, Nicholas M; Barber, Bridget E
Abstract: Background: Plasmodium knowlesi causes severe and fatal malaria, and incidence in Southeast Asia is increasing. Factors associated with death are not clearly defined. Methods: All malaria deaths in Sabah, Malaysia, from 2015 to 2017 were identified from mandatory reporting to the Sabah Department of Health. Case notes were reviewed, and a systematic review of these and all previously reported fatal P. knowlesi cases was conducted. Case fatality rates (CFRs) during 2010–2017 were calculated using incidence data from the Sabah Department of Health. Results: Six malaria deaths occurred in Sabah during 2015–2017, all from P. knowlesi . Median age was 40 (range, 23–58) years; 4 cases (67%) were male. Three (50%) had significant cardiovascular comorbidities and 1 was pregnant. Delays in administering appropriate therapy contributed to 3 (50%) deaths. An additional 26 fatal cases were included in the systematic review. Among all 32 cases, 18 (56%) were male; median age was 56 (range, 23–84) years. Cardiovascular-metabolic disease, microscopic misdiagnosis, and delay in commencing intravenous treatment were identified in 11 of 32 (34%), 26 of 29 (90%), and 11 of 31 (36%) cases, respectively. The overall CFR during 2010–2017 was 2.5/1000: 6.0/1000 for women and 1.7/1000 for men ( P = .01). Independent risk factors for death included female sex (odds ratio, 2.6; P = .04), and age ≥45 years (odds ratio, 4.7; P < .01). Conclusions: Earlier presentation, more rapid diagnosis, and administration of intravenous artesunate may avoid fatal outcomes, particularly in females, older adults, and patients with cardiovascular comorbidities. Abstract : Six deaths from Plasmodium knowlesi malaria in Sabah, Malaysia in 2015–2017 and 26 previously reported deaths were reviewed. Associated factors included female sex; age ≥45 years; cardiovascular-metabolic comorbidities; and delays in presentation, diagnosis, and treatment.